(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction : The treatment of severe acne scars is challenging due to the variety in morphology of acne scars and the limitations of the available treatment modalities in their ability to improve scars. Tailored treatment plan must be created in which the patient’s specific types of scars are treated with the procedures that are most likely to improve those types of scars. This study aims to assess the efficacy of combination therapy using subcision, platelet rich plasma therapy, microneedling and spot 50% TCA CROSS in the management of grade 3 and 4 atrophic scars. Method: Twenty one patients with grade 3 or 4 atrophic acne scars were graded using Goodman and Baron Qualitative grading. Subcision, Platelet Rich Plasma therapy, microneedling and spot 50% TCA CROSS were performed in single sitting for three sessions 1 month apart. Grading of acne scar photographs was done pretreatment and 1 month after last procedure. Result: Out of 10 patients with Grade 4 scars, 3 patients improved to Grade 2, 6 patients improved to Grade 3 and 1 patient improved to Grade 1 scars. Out of 11 patients with Grade 3 scars, 1 patient was left with no scars, 3 patients improved to Grade 1 and 7 patients improved to Grade 2. Conclusion: This combination Subcision, PRP, Micro-needling and TCA CROSS, if they are combined and adequately done in proper manner has shown good results in treating severe Grade 4 and 3 scars.